2000
DOI: 10.1093/toxsci/54.1.154
|View full text |Cite
|
Sign up to set email alerts
|

Estrogenic Activity of Octylphenol, Nonylphenol, Bisphenol A and Methoxychlor in Rats

Abstract: Considerable attention has recently been focused on environmental chemicals that disrupt the reproductive system by altering steroid receptor function. Although numerous in vitro and in vivo methods have been shown to be useful approaches for identifying chemicals that can disrupt reproduction through a direct interaction with the estrogen receptor, it is imperative that the protocols selected be capable of detecting chemicals with a broad range of estrogenic activity. Here we evaluate the reliability of the 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
263
3
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 522 publications
(281 citation statements)
references
References 51 publications
13
263
3
2
Order By: Relevance
“…In rats, BPA produces a variety of hormone-like effects (Laws et al, 2000;Long et al, 2000 ). The health effects of BPA exposure on humans have not been studied.…”
Section: Discussionmentioning
confidence: 99%
“…In rats, BPA produces a variety of hormone-like effects (Laws et al, 2000;Long et al, 2000 ). The health effects of BPA exposure on humans have not been studied.…”
Section: Discussionmentioning
confidence: 99%
“…The most common short-term in vivo assay for (anti)estrogenicity is the uterine growth test, suitable for screening ERα agonists and antagonists. Either immature intact or adult ovariectomized female rats or mice are used (Odum et al, 1997;Kang et al, 2000;Laws et al, 2000;Cotroneo et al, 2001;Newbold et al, 2001;Kanno et al, 2003). The test compounds are administered either subcutaneously or orally for a period of 3-7 days.…”
Section: Testing Estrogenicity Testing Estrogenicity Testing Estrogenmentioning
confidence: 99%
“…The delay of nonylphenol excretion is possible because of the adverse effects of nonylphenol on rat reproductive systems (Laws et al, 2000).…”
Section: Fig 5 Excretion Of Alkylphenol Metabolites During Liver Pementioning
confidence: 99%
“…Early neonatal exposure to nonylphenol has been reported to cause dysfunction of postpubertal reproductive function in female rats as well as disrupted development of gonads in male and female rats (Nagao et al, 2000). It has also been reported that nonylphenol administered orally at a dose of 50 mg/kg of body weight induced a significant increase in uterine weight of prepubertal rats and advanced the age of vaginal opening (Laws et al, 2000). Elucidation of the metabolism and fate of nonylphenol is important for estimating the risks of the chemical for animals.…”
mentioning
confidence: 99%